As crenças dos professores surdos de Manaus: perspectivas e desafios - Gomes, Roberta Spener (Brasil, 2024)
This sought to understand the beliefs, perspectives and challenges of hearing learning Libras as a second language (L2). To do this, we conducted interviewed 6 deaf teachers, aged between 20 and 50, They answered flexible questions aimed at understanding the process of teaching and communication between hearing students, through courses such as CEL (Center for Language Studies) and others. To this end, we looked to theorists on beliefs in language teaching, such as BARCELOS 2006, and the teaching of Libras to hearing teaching, such as GESSER, 2012 and other national researchers. The results revealed that these beliefs of deaf teachers are capable of teach LIBRAS to hearing students, because Libras really is a language with its own linguistic structure. with its own linguistic structure. However, they believe that learning Libras can contribute positively to their professional training. their professional training.